Historical Development of Education and Science in Serbia from the Late 18th Century and the First Half of the 19th Century - Ivković, Nikola M.; Maksimović, Nebojiša M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The work focuses on the period of the late 18th and early 19th centuries. The research observes the prism of the origin of the Serbian state and, in this connection, the development of science is crucially considered. The emergence of modern science in the geographical area where Serbs lived can be observed and followed in fragments from the Middle Ages to modern times. The period from XV to XVIII, however, marked almost complete stagnation in all fields, including science. The Ottoman occupation interrupted the development of the intellectual thought of the Middle Ages and thus separated the Serbian people from the continuity of intellectual ideals. The modern beginning of scientific development is chronologically connected with the uprisings of 1804 and 1815. The events that triggered the turmoil in the 18th century were the basis for the development of science and its highest level through the early 19th century. This is precisely why observing the development of science in the chronological period of the late 18th and early 19th centuries reveals the foundations of modern education in our country. In order to understand and perceive the context, the paper also refers to the earlier periods of Serbian statehood and science. A comparative presentation of European science and chronology is important for broader connotations and understanding of a partial global historical flow. The paper concludes that the development of statehood in Serbia was closely related to the development of science, and that the key participants in those processes understood the importance of the qualifications of state managers and the very creation of a nation. Competence, in that sense, was understood as the scientific progress of the individual, and thus of the community. The emergence of the modern Serbian state was imbued with the development of science as a basic component of the establishment of modern administration. The statesmen realized that in addition to force, there must also be reason, which will direct the direction of the functioning of the young state. Since Karađorđe, the mechanisms of creation and establishment of scientific foundations are already being launched. For this purpose, the Great School was founded as a forerunner of the highest level of education and nurturing of science. The circumstances of the time and political events influenced the shift of the center of gravity of the highest system of scientific education and work to the new capital - Kragujevac. Kragujevac has become a new place of beginning and creation of the highest levels of knowledge.